Risk Factors for Post-Transplant Death in Donation after Circulatory Death Liver Transplantation. (3rd September 2018) - Liu, Song; Miao, Ji; Shi, Xiaolei; Wu, Yafu; Jiang, Chunping; Zhu, Xinhua; Wu, Xingyu; Ding, Yitao; Xu, Qingxiang
ABSTRACT: Purpose : In spite of the increasing success of liver transplantation, there remains inevitable risk of postoperative complications, re-operations, and even death. Risk factors that correlate with post-transplant death have not been fully identified. Materials and Methods : We performed a retrospective analysis of 65 adults that received donation after circulatory death liver transplantation. Binary logistic regression and Cox's proportional hazards regression were employed to identify risk factors that associate with postoperative death and the length of survival period. Results : Twenty-two recipients (33.8%) deceased during 392.3 ± 45.6 days. The higher preoperative Child–Pugh score ( p = .007), prolonged postoperative ICU stay ( p = .02), and more postoperative complications ( p = .0005) were observed in deceased patients. Advanced pathological staging ( p = .02) with more common nerve invasion ( p = .03), lymph node invasion ( p = .02), and para-tumor satellite lesion ( p = .01) were found in deceased group. The higher pre-transplant Child–Pugh score was a risk factor for post-transplant death (OR = 4.38, p = .011), and was correlated with reduced post-transplant survival period (OR = 0.35, p = .009). Nerve invasion was also a risk factor for post-transplant death (OR = 13.85, p = .014), although it failed to affect survival period. Conclusions : Our study emphasizes the impact of recipient's pre-transplant liver function as well as pre-transplant nerve invasion by recipient's liver cancer cells on postoperative outcome and survival period in patients receiving liver transplantation.